Combining ability of phenological traits and seed yield in spring rapeseed genotypes - Rameeh, Valiollah (Plant Breeding and Seed Science, 2015)
Six parents and their 15 F2 diallel progenies, totally 21 genotypes, were evaluated for genetic parameters of quantitative characteristics. The traits of interest were growing degree days (GDDs) from sowing to the flowering (DDF), to end of flowering (DDE), flowering period (DFP), to maturity (DDM) and seed yield (SY). Significant mean squares of general combining ability (GCA) was exhibited for DDF, DDE, DFP, DDM and seed yield indicating significant differences of GCA effects of parents for these traits. Significant mean squares of specific combining ability (SCA) for all the traits exhibited the importance of non additive genetic effects for the traits. Significant ratio of MS(GCA)/MS(SCA) and high narrow sense heritability estimates for DDF, DDE, DDM indicating the prime importance of additive genetic effects for controlling these traits. DFP was also less heritable than the other phonological traits, so the efficiency of selection for this trait will be low. All of the combinations with significant negative SCA effects for DDM had at least one parent with significant negative GCA effect for this trait. PF7045/91 with significant positive GCA effect of SY, was best combiner for improving SY. Significant positive correlation between DDM and each of two traits including DDF and DDE, indicating these traits can be used as indirect selection criteria for improving DDM.